Pengaruh Penerapan Terapi Lidah Buaya Terhadap Tingkat Keparahan Pruritus Pada Lansia Dermatitis Atopik di Seksi Kesejahteraan Sosial Paduwau Maumere - Yosepina Meliana; Maria Lambertina Barek Aran (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Dermatitis is characterized by itchy, dry, reddish pruritic skin which can cause swelling, uncomfortable and infection in the scratch wounds. The aim of this study was to determine the effect of aloe vera compresses on the severity of pruritus in elderly dermatitis. The design of this research is a descriptive case study with a bleeding process approach. The subjects in this case study were 2 elderly. Management of dermatitis is carried out with a combination of pharmacological and non-pharmacological treatments. Pharmacological with betamethasone and non-pharmacological with aloe vera gel compress therapy and skin care education. The severity of pruritus was measured using the standard pruritus severity scale instrument. Applying surgical intervention with aloe vera compress therapy can overcome the problem of pruritus and improve skin integrity in both subjects with dermatitis. Subject 1 before the intervention was in the severe itching category becoming the moderate itching category during the evaluation after the intervention. Subject 2 before the intervention was in the moderate itching category to the mild itching category during the evaluation after the intervention.